Experimental Study on the Transition Characteristics and Criterion From Wall-Peak to Core-Peak Phase Distribution in Vertical Rod Bundles - Ren, Quan-yao; Pu, Zengping; Chen, Ping; Pan, Liang-ming; Zhu, Fawen; Zheng, Meiyin; Wang, Haoyu; Wei, Lie; He, Hui (Frontiers in Energy Research, 2021)
Aiming to understand the phase distribution characteristics and develop the transition crite-ria from wall-peak to core-peak phase distribution in rod bundle channel, air-water two phase flow experiments have been conducted in 5×5 rod bundles on the Gas-Liquid two phase flow and Interfacial Evolution Research Facility at Chongqing University (GLIERFC). Based on the experimental result, the influences of gas and liquid velocity, mixing vane spacer grid (MVSG), system pressure and geometrical size on phase distribution have been analyzed in detail. With the superficial gas velocity increasing and liquid velocity decreas-ing, the wall-peak phase distribution would turn to core-peak. And the MVSG would delays the transition occurring. The gap size is vital in the phase distribution in rod bundles. On the basis of the analysis on the influencing factors, the transition criteria from wall-peak to core-peak phase distribution has been developed based on the experimental result and open-published data in the literature.